Ultraviolet Quantum Cutting through down Conversion Luminescence Behaviour of Er3+ Substituted Sr0.7Bi2.2Nb2O9 (BLFS) Ceramics. Issue 204 (2nd January 2020) - Tomar, Amit; Singh, Meetesh; Singh, Suram; Sharma, Lokesh; Arya, Sandeep; Kasana, Sanyogita
Abstract: In the present work, we studied the down conversion luminescence behavior of Er 3+ substituted Sr0.7 Bi2.2 Nb2 O9 bismuth layered ceramics (SBN-xEr, x = 0.0, 0.6, 0.8, 1) prepared by improved solid state reaction method. Different Characterization techniques like Powder X-Ray Diffraction (P-XRD), Field Emission Scanning Electron Microscopy (FE-SEM) and Photoluminescence (PL) were used to examine the structural, morphological and optical properties of the as prepared samples respectively. A FE-SEM image clearly shows the change in grain size for undoped and doped samples. The PL spectra of these samples suggest a presence of four intense emission bands of different wavelengths peaking around 450 nm (violet), 475 nm (blue), 525 nm (green), and 540 nm (green) under UV light excitation (280 nm). The Er 3+ substituted Sr0.7 Bi2.2 Nb2 O9 bismuth layered ceramics facilitate in a productive harvesting of Ultra-Violet to visible radiation for energy conversion processes and it might be applied to UV sensor applications.